2022
DOI: 10.3389/fgwh.2022.819953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic and Telehealth on Antenatal Screening and Services, Including for Mental Health and Domestic Violence: An Australian Mixed-Methods Study

Abstract: IntroductionAustralian antenatal care includes specific screening and service provision for domestic and family violence (DFV) and mental health. However, the COVID-19 pandemic resulted in major care changes, including greatly expanded telehealth. Given difficulties in a safe assessment and management of disclosures via telehealth, DFV and mental health service provision might be substantially impacted. This study therefore aimed to assess COVID-19 effects on DFV and mental health screening, as well as broader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…10 full-text studies were ultimately included in this review (see figure 1). Three lead authors were contacted for additional data and clarification regarding findings specific to midwives 22–24…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…10 full-text studies were ultimately included in this review (see figure 1). Three lead authors were contacted for additional data and clarification regarding findings specific to midwives 22–24…”
Section: Resultsmentioning
confidence: 99%
“…The 10 studies meeting the review inclusion/exclusion criteria represented the views of 3354 midwives regarding telehealth in their midwifery practice. Of the 10 selected studies, 3 studies reported the telehealth experience of multiple types of providers (physicians, nurses, midwives), therefore only data pertinent to midwives was extracted 22–24 Tables 2 and 3. show the characteristics of each included study and table 4 displays the key thematic findings for each study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations